2006
DOI: 10.1002/acp.1264
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of involuntary autobiographical memory retrievals

Abstract: This study compared three different ways autobiographical memories are elicited involuntarily: (1) cued by an active goal common to memory and retrieval contexts in combination with sensory information associated with this goal-directed activity; (2) cued by sensory information that does not relate to goal-directed activity common to both memory and retrieval contexts; and (3) activated when no identifiable cue present in retrieval context. Two hundred and twenty eight participants recorded details of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 20 publications
5
71
2
Order By: Relevance
“…Specifically, as secondary tasks are added to ongoing activities, thereby requiring more attentional resources, individuals may set a higher threshold for allowing cue-driven thoughts unrelated to the ongoing tasks to enter consciousness. This notion is consistent with the idea that spontaneously retrieved memories (memories that occur without a deliberate search) are more likely to reach consciousness when we are relaxed and our attention is not highly focused (Ball & Little, 2006;Kvavilashvili & Mandler, 2004). Even if retrieval were not challenged by demanding ongoing activities, demanding ongoing activities could compromise execution of the prospective memory intention by interfering with its maintenance in awareness until execution was possible (see Einstein et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, as secondary tasks are added to ongoing activities, thereby requiring more attentional resources, individuals may set a higher threshold for allowing cue-driven thoughts unrelated to the ongoing tasks to enter consciousness. This notion is consistent with the idea that spontaneously retrieved memories (memories that occur without a deliberate search) are more likely to reach consciousness when we are relaxed and our attention is not highly focused (Ball & Little, 2006;Kvavilashvili & Mandler, 2004). Even if retrieval were not challenged by demanding ongoing activities, demanding ongoing activities could compromise execution of the prospective memory intention by interfering with its maintenance in awareness until execution was possible (see Einstein et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…To resolve the spontaneous familiarity in the "butcher-in-the-bus" example, consciously-controlled processing was necessary to identify the familiar person as being the butcher. In naturalistic settings, there are similar occasions wherein spontaneous familiarity is not resolved and one is left unable to identify why something seems familiar (Ball & Little, 2006;Berntsen, 2010;Kvavilashvili, & Mandler, 2004). In this article, our focus is on involuntary familiarity of the butcher-in-the-bus variety although more complete forms of involuntary memory might also contribute to our results.…”
Section: Introductionmentioning
confidence: 87%
“…For example, younger adults may spontaneously recognize distracting information when the target of the memory task frequently switches to the previously distracting stimulus type during test, making it more difficult to constrain retrieval processes. Further, involuntary memory in daily life has been reported to occur across a variety of contexts that vary in the extent to which memory is actively engaged in the ongoing task (e.g., Ball & Little, 2006). Another important question is whether spontaneous familiarity operates in a similar way when it occurs outside of a memory task.…”
Section: Discussionmentioning
confidence: 99%
“…second, the majority of memories are elicited by d easily identifiable cues, most of which correspond to and form central features of the memory content (Berntsen, 1998;Berntsen & Hall, 2004;Schlagman et al, 2007). Cues have also been found to be predominantly external (i.e., present in the environment), as opposed to internal thoughts (Ball & Little, 2006;Berntsen, 1998;Berntsen & Hall, 2004;Kvavilashvili & Mandler, 2004;Mace, 2004;Schlagman et al, 2007). Furthermore, Berntsen (2007) reported that the majority of external cues from her 1998 diary study (i.e., 66%) were peripheral aspects of the envit ronment-that is, aspects of the environment that were not directly related to the current activity of the rememberer.…”
mentioning
confidence: 99%